Generation Y employees in the banking sector in Malaysia: social needs, intention to stay and perceived organizational support - Zabedah Othman; Jugindar Singh Kartar Singh; Raemah Abdullah Hashim (Readers Insight Publisher, 2019)
By year 2025, 75% of the workforce will be Gen Y employees. This study examined the influence of social needs on the intention to stay by Gen Y employees in the banking sector in Malaysia. The mediation role of perceived organizational support between the two constructs was examined. In this quantitative study, primary data was collected from a sample of 470 respondents. The examination concluded that higher level of social needs had a positive and significant influence on intention to stay. This study further revealed that perceived organizational support partially mediated the relationship between social needs and intention to stay. Due to the expected rise of the Gen Y workforce in future, this study will give organizations a better understanding and knowledge of Gen Y social needs and provide them the right tools to collaborate and find the right solutions. (Abstract by authors)